Effect of feeding marua (Eleusine coracana) as an energy source in the grower ration of Large White Yorkshire piglets - HARI, U K; SINHA, A P; SINGH, S K; SRIVASTAVA, J P (The Indian Journal of Animal Sciences, 2013)
Energy is the largest and Important component of swine diets. Marua may be used in pig rations as an energy source in order to reduce the cost of raising pigs vis·a-vis the cost of production. The present study was carried out on 2·month· old 32 Large White Yorkshire piglets maintained at Government Pig Breeding Farm, Kanke, Ranchi, Bihar. The control group (T1) was fed a standard diet (18-19% protein, 60% maize). The experimental groups (T2/sub> to T4) were fed the diets in which maize was replaced with mania at 33.3,66.6 and 100% (w/w). Significantly higher total weIght gain was recorded in T4 and T3 than T2 and T1 In 20 weeks of experimental period. The feed gain ratios varied from 4.39 (T,) to 3.78 (T4) did not differ significantly. The cost per kg of weight gam in T, to T. diet was Rs 15.05, 13.57, 11.19 and 9.79 respectively. Effect of treatment on DM intake was nonsignificant but its effect on DM digestibility was significant. DM digestibility of T4 was significantly higher than rest of the groups. OCP, TDN, DE and ME values varied between normal limits among groups. Nonsignificant effects were observed with respect of DCP but on the contrary effect of treatment on TDN, ME and DE was highly significant. All the animals were in positive N, Ca and P balances. It was thus, concluded that marna could successfully and economically replace maize in pig growing ration.